VARIABEL PENENTU KEPUTUSAN PEMBAGIAN DIVIDEN PADA PERUSAHAAN YANG GO PUBLIK DI INDONESIA PERIODE 2000-2002 (Tinjauan Terhadap Signaling Theory) - Bahtiar Usman (Media Riset Bisnis & Manajemen, 2006)
The purpose of this research is to observe determinant factors for dividend policy and to analyze wether signalling theory can influence dividend policy for go public companies in Indonesia. The sample is all company listed in LQ45 which distribute cash dividend at 2000 and still distribute it at 2002. Empirically, it found that, cash dividend policy in go public companies in Indonesia is influenced by profitability, certanty investation probability, firm size and capital structure. Moreover, "signaling theory' which is rise up by Aharony and Swary (1980) not fully applicable for go public companies in Indonesia.